Bidirectional naming emergency in children with cochlear implant via Multiple Exemplar Instruction (MEI) (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
The purpose of this study was to verify the required number of exposures to the Multiple Exemplar Instruction (MEI) procedure for the emergence of bidirectional naming repertoire in a 13-year-old girl with a cochlear implant for 1 year. Stimuli consisted of three sets of five pictures (visual stimuli) and their respective names (auditory stimuli), which were used in four phases: (1) evaluation of speaker and listener repertoires; (2) listener training and first bidirectional naming test; (3) MEI training; and (4) second bidirectional naming test. For sets of stimuli 1 and 2, results showed that listener training alone did not produce the emergence of tacts. Percentage of correct listener responses was higher than percentage of correct speaker responses. Tacts were observed after successive MEI training sessions. Two exposures to the MEI training produced equal percentage of correct responding for both listener and speaker repertoires. For set of stimuli 3, results showed that listener training alone was sufficient for the emergence of tacts. The study suggests that MEI training promoted the shared control of stimuli and the emergence of bidirectional naming (hearing and pointing to the picture; vocally naming the picture with correspondence with the auditory stimuli).
Keywords: bidirectional naming; multiple exemplar instruction; cochlear implant